34.4k views
11 votes
Solve using elimination.

–9x − 9y = –18

8x + 9y = 20

Solve using elimination.

–9x − 9y = –18

8x + 9y = 20

Solve using elimination.

–9x − 9y = –18

8x + 9y = 20

Solve using elimination.

–9x − 9y = –18

8x + 9y = 20

Solve using elimination.

–9x − 9y = –18

8x + 9y = 20



User Mokagio
by
4.8k points

1 Answer

9 votes
The process and the answer is shown in the following picture. The five ones are all the same.
Solve using elimination. –9x − 9y = –18 8x + 9y = 20 Solve using elimination. –9x-example-1
User Pettis Brandon
by
5.3k points